Tinjauan Pustaka: Analisis Manajemen Logistik pada Instalasi Gizi - Nurhidayah Tiasya Sanas; Ma’rifat Istiqa Mukty (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Effective and efficient logistics management at the Nutrition Installation is an important factor in ensuring the availability and quality of food for patients. This study aims to analyze logistics management in nutritional installations. The method used is the content analysis method by searching 10 reviews in various health journal sources in Indonesia for the past 10 years. The results of an integrated literature review explain that logistics management in the Nutrition Installation ensures the availability and quality of food for patients. Logistics management includes storage systems, distribution systems, budget systems required annually or monthly. Several logistics management processes in each hospital are different but run well, even though there are many shortcomings. Logistics management at Nutritional Installations is carried out optimally by increasing the accuracy of planning food needs, procuring food ingredients appropriately, improving food storage standards, timely distribution of food, and carrying out regular monitoring and evaluation, making it easier for health workers to carry out their duties and minimize undesirable events.